ANALISIS PENYEBAB KETERLAMBATAN ARSITEKTUR PROYEK APARTEMEN DENGAN METODE FAULT TREE ANALYSIS - Tasya Nabilah; I Ketut Sucita (Prokons: Jurnal Teknik Sipil, 2022)
AbstractConstruction project work is one of the main sectors that are important in economic development. When the implementation of the project takes place, there are 3 important things that need to be taken into account, namely covering cost, time and quality. A project is declared successful when it has fulfilled these three things. Construction delays are considered one of the recurring obstacles in the construction industry and have an adverse effect on the success of the project. In the construction project Apartment 'X' experienced delays for architectural work with a deviation of -48.359% in February 2021. This study describes the delay in architectural work based on human factors, management factors and other factors. The purpose of the study was to determine the probability of delay with the Fault Tree Analysis (FTA) method.The priority of using the FTA method is to be able to analyze the causes of failures in a system in detail, structured and easy to understand. Data collection was carried out by distributing questionnaires as many as 19 project respondents who had met the research criteria. The results showed that the probability of delay for architectural work was 0.921 with the dominant factor being the human factor caused by repair and rework work with a probability of 0.309. That is, the possibility of delays in architectural work occurs because of the variables listed.Keywords: Fault Tree Analysis, Project Delays, Causes and Impacts of Delays